2018
DOI: 10.4103/ijabmr.ijabmr_447_16
|View full text |Cite
|
Sign up to set email alerts
|

Effect of short-term consumption of amul probiotic yogurt containing Lactobacillus acidophilus La5 and Bifidobacterium lactis Bb12 on salivary streptococcus mutans count in high caries risk individuals

Abstract: Aim:This study aims to study the effect of short-term consumption of probiotic yogurt containing Lactobacillus acidophilus La5 and Bifidobacterium lactis Bb12 on salivary Streptococcus mutans count in high caries risk individuals.Materials and Methods:A double-blind randomized control trial was conducted, and 70 high caries risk individuals with a salivary S. mutans count of more than 106 CFU/ml of saliva were followed for 4 weeks. Participants ingested 100 g yogurt containing L. acidophilus La5 and Bifidobact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(19 citation statements)
references
References 16 publications
(13 reference statements)
1
16
0
2
Order By: Relevance
“… Brasili et al (2013) found that the supplementation of this probiotic induced a positive modulation of urinary and fecal metabolic profiling thus suggesting a possible effect on the prevention and/or the reduction of age-related metabolic dysfunction, while Zarrati et al (2013) reported a significant modulation on T-cell subset specific gene expression in peripheral blood mononuclear cells among overweight and obese individuals. Other probiotic effects include the inhibition of Escherichia coli O157:H7 ( Medellin-Peñna and Griffiths, 2009 ), and the reduction of Streptococcus mutans in saliva ( Bafna et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“… Brasili et al (2013) found that the supplementation of this probiotic induced a positive modulation of urinary and fecal metabolic profiling thus suggesting a possible effect on the prevention and/or the reduction of age-related metabolic dysfunction, while Zarrati et al (2013) reported a significant modulation on T-cell subset specific gene expression in peripheral blood mononuclear cells among overweight and obese individuals. Other probiotic effects include the inhibition of Escherichia coli O157:H7 ( Medellin-Peñna and Griffiths, 2009 ), and the reduction of Streptococcus mutans in saliva ( Bafna et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…Previously, Bafna et al . [ 9 ] have done a study on the effect of short-term consumption of probiotic yogurt containing L. acidophilus La5 and Bifidobacterium lactis Bb12 on salivary S. mutans count in high caries risk individuals. They found that there was a statistically significant reduction of salivary S. mutans , which was recorded after probiotic yogurt consumption with minimal residual effect.…”
Section: Discussionmentioning
confidence: 99%
“…FB-T9 exhibited excellent efficacy in both the prevention and treatment groups and demonstrated that a potential probiotic could outperform chlorhexidine in the treatment of dental caries (Table 3). Current studies have shown that probiotic products can reduce the population of S. mutans in the human oral cavity [42,43].…”
Section: Discussion/conclusionmentioning
confidence: 99%